Ectosomes released by platelets induce differentiation of CD4+ T cells into T regulatory cells - Sadallah, Salima; Amicarella, Francesca; Eken, Ceylan; Iezzi, Giandomenica; Schifferli, Jürg A. (Thrombosis and Haemostasis, 2014)
Accumulating evidence suggests an immune-modulatory role for platelets (PLT) and PLT-derived microvesicles. In particular, ectosomes, i.e. vesicles budding from PLT surface, have been shown to exert immunosuppressive activities on phagocytes. Here we investigated the effects mediated by PLT-derived ectosomes (PLT-Ecto) on CD4+ T cells. Exposure of activated CD4+ T cells to PLT-Ecto decreased their release of IFNγ, TNFα and IL-6, and increased the production of TGF-β1. Concomitantly, PLT-Ecto-exposed CD4+ T cells displayed increased frequencies of CD25high Foxp3+ cells. These phenomena were dose-dependent and PLT-Ecto specific, since they were not observed in the presence of polymorphonuclear- and erythrocyte-derived ectosomes. Analysis of specific T cell subsets revealed that PLT-Ecto induced differentiation of naïve T cells into Foxp3+ cells, but had no effect on predifferentiated Foxp3+ regulatory T cells (Tregs). Importantly, PLT-Ectoinduced Foxp3+ cells were as effective as peripheral blood Tregs in suppressing CD8+ T cell proliferation. PLT-Ecto-mediated effects were partly dependent on PLT-derived TGF-β1, as they were to some extent inhibited by PLT-Ecto pretreatment with TGF-β1-neutralising antibodies. Interestingly, ectosome-derived TGF-β1 levels correlated with Foxp3+ T cell frequencies in blood of healthy donors. In conclusion, PLT-Ecto induce differentiation of CD4+ T cells towards functional Tregs. This may represent a mechanism by which PLT-Ecto enhance peripheral tolerance.
Keywords: Microparticles; ectosomes; extracellular vesicles; platelet immunology; T cell differentiation